Mechanical strength of thermally aged Sn-3.5Ag/Ni-P solder joints - He, Min (2012)
This work presents an investigation on the influence of the solder/under bump metallization (UBM) interfacial reaction to the tensile strength and fracture behavior of Sn-3.5Ag/Ni-P solder joints under different thermal aging conditions. The tensile strength of Sn-3.5Ag/Ni-P solder joints decreases with aging temperature and duration. Four types of failure modes have been identified. The failure modes shift from the bulk solder failure mode in the as-soldered condition toward the interfacial failure modes. Kirkendall voids do not appear to affect the tensile strength of the joint. The volume change of Ni-P phase transformation during the thermal aging process generates high tensile stress inside the Ni-P layer; this stress causes mudflat cracks on the remaining Ni-P coating and also leads to its delamination from the underlying Ni substrate. In general, interfacial reaction and the subsequent growth of Ni3Sn4 intermetallic compound (IMC) layer during solid-state reaction are the main reasons for the decrease of tensile strength of the solder joints. The current study finds there is an empirical linear relation between the solder joint strength and the Ni3Sn4 intermetallic compound (IMC) thickness. Therefore, the IMC thickness may be used as an indication of the joint strength.